Aplicação do Modelo Swat na avaliação do consumo de água em áreas de florestas plantadas na bacia do rio Pará, Alto São Francisco, em Minas Gerais / Application of SWAT Model in the evaluation of water consumption in planted forest areas in Pará river basin, Upper São Francisco, in Minas Gerais. - Evandro Luís Rodrigues; Marcos Antônio Timbó Elmiro; Claudia Maria Jacobi; Wanderson Lopes Lamounier (Sociedade & Natureza)
Forests are very important for the balance of the hydrological cycle. There is, however, a discussion on whether plantations increase exaggeratedly water consumption in watersheds, especially if such plantations replace original smaller-size vegetation such as in the cerrado. This study aimed to investigate the influence of reforestation in maintenance and balancing the hydrological cycle in the basin of the Pará River, Upper San Francisco, Minas Gerais, using the hydrological model SWAT. The results show the efficiency of environmental modeling as a method to detect impacts on water balance due to changes in vegetation cover. The diagnosis revealed a reduction of 4.26% in the scenario of bushland use, 9.68% on average reforestation scenario, and 11.59% in the intensive reforestation. The retention curve suggests the existence of large natural storage indicating a high degree of resilience of the hydrological behavior. Besides plant cover, the results also indicate a close influence of physical and climatic variables in governing water production in the basin. The results generated by the SWAT model were satisfactory, producing reliable and meaningful estimates for the analyses. It is noteworthy that the model adequately considered the variables in its structure, showing its effectiveness in consistently representing the behavior of the basin according to the spatial and temporal distribution. Thus, the results indicate that changes in the short and medium term in the use and land cover in a watershed can cause either higher or lower impacts depending on the physical and climatic variables of water regime.